The impact of BIM authoring tools on the architectural profession in Jordan - Al-Ruawishedi, Mais Radhi; Qaqish, Raed; Azzam, Esam; Khraisat, Dema; AlOmari, Omar Moustafa Ahmad (project baikal, 2023)
Building Information Modeling (BIM) technologies have attracted much research attention, especially in the last fifteen years. The prospects and benefits that BIM promises for all participants in the design, construction and operation of buildings are hopeful and enthusiastic. Nevertheless, the global adoption of BIM has been slow and uneven. A bibliometric analysis shows that BIM research is concentrated in a few centers and performed by a narrow group of specialists. As a result, there are research areas with few or no publications (“blind spots”). One such area is the economics of BIM implementation. Considering the transition to the use of BIM as an investment project, the authors of the article formulate the necessary conditions for BIM implementation to become investment attractive. It is shown that the participation of governmental structures is necessary for a wide transition to digital technologies in the architectural and construction sphere.
Keywords: architecture; construction; BIM; investment; Jordan